Percutaneous Dilatational Tracheostomy; Diagnosis and Mortality Rate in Intensive Care Saiful Anwar Hospital - Ariady, Randika Rea; Wiwi Jaya; Arie Zainul Fatoni; Isngadi; Aswoco Andyk Asmoro (Journal of Anesthesiology and Clinical Research, 2024)
Introduction: Tracheostomy is a common surgical procedure performed on critically ill intensive care patients. Reports have documented considerable associated morbidity, with complication rates varying from 6 to 66%. The reports on mortality associated with tracheostomy range from 0 to 5%. Since its introduction, percutaneous dilatational tracheostomies (PDT) have gained increasing popularity. The most commonly cited advantages are the ease of the familiar technique and the ability to perform the procedure at the bedside.7 This paper aims to study the mortality rate and diagnosis of patients who performed the percutaneous dilatational tracheostomy procedure in the ICU of Saiful Anwar Malang Hospital. Methods: Observational analytical research is carried out cross-sectionally. Data was collected from the medical records of patients undergoing PDT for the period July 2022 – October 2022. Statistical analysis using the Chi-square test. Results: From 39 subjects, 34 (87.2%) subjects experienced respiratory failure. The most common cause was HAP pneumonia (61.5%), followed by CVA (17.9%) and CAP pneumonia (12.8%); the rest were EDH, SAH, and ASD secundum, as much as 2.6%. The outcome was that 13 (33.3%) subjects died, and the rest survived and were transported to a care ward. Correlation between patient outcomes with respiratory failure p=0.735, with diagnosis p=0.309. Conclusion: The most common diagnosis of PDT is HAP pneumonia. There was no significant correlation between diagnosis and mortality of patients performed by PDT.